Clinical condition of patients with Obesity Hypoventilation Syndrome (OHS): case report - Made Oka Heryana; Heru Widjono (Jurnal Teknologi Laboratorium)
Abstract. Obesity hypoventilation syndrome (OHS) or Pickwikian's syndrome consists of obesity, breathing-related sleep disturbances, and chronic daytime hypoventilation. Identifying OHS is essential due to the risk of clinical exacerbation leading to respiratory failure and the high mortality rate among untreated patients. A 55-year-old woman was admitted to the emergency room with two days of weakness and fatigue. She is unable to perform daily tasks due to shortness of breath. She was recently diagnosed with diabetes. The patient weighs 133 kilograms and has a height of 155 centimeters (Body Mass Index of 55,4 kg/m2). The patient's blood glucose was 351 mg/dl, with an abnormal result of HbA1C of 11.5%. The blood pressure tends to stage 1 hypertension, and arterial blood gas examination showed respiratory acidosis. We diagnosed her with obesity hypoventilation syndrome, type 2 diabetes, and stage 1 hypertension. During her five-day hospitalization, her condition improved. Correct diagnosis and management can improve the patient's quality of life and decrease the risk of comorbidities. In addition, it can reduce the cost and time of hospital care.